Food sovereignty and agro-ecology in Karnataka: interplay of discourses, identities, and practices. Issue 4 (19th May 2017) - Bhattacharya, Niloshree
ABSTRACT: Karnataka Rajya Raitha Sangha (KRRS), a farmers' movement, and a member of La Via Campesina, has been encouraging zero-budget natural farming in Karnataka, India, within the framework of food sovereignty and agro-ecology. Using the experiences of KRRS, this article addresses the question of the extent of pluralism within the discourse of food sovereignty. Focusing on the interplay of local and global practices, discourses and identities, the article throws light upon contradictions and negotiations between "necessary abstractions" and "particularisms", spaces and places of resistance and implications it may have on struggles at both local and global levels.